2010
DOI: 10.1007/s10764-010-9417-3
|View full text |Cite
|
Sign up to set email alerts
|

Home-range Use by a Large Horde of Wild Mandrillus sphinx

Abstract: The predicted relationship between home-range size and group mass in primates developed by Clutton-Brock and Harvey (1977) has proved extremely robust in describing the use of space by most primate species. However, mandrills (Mandrillus sphinx) are now known to have an extreme group mass in the wild, far larger than that of the species used originally to generate that relationship, and so it was unknown whether this relationship would be robust for this species. We investigated the home-range size and use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 58 publications
(67 reference statements)
0
23
0
Order By: Relevance
“…Mandrills ( Mandrillus sphinx ) live in tropical rainforests and in gallery forests adjacent to savannas, as well as rocky forests, riparian forests, cultivated areas and flooded forests and streambeds. Forest-dwelling mandrills mostly feed (over 70% year-round) on mechanically protected plant foods such as hard-shell fruits or seeds from the ground [86,87], but will also eat leaves, lianas, bark, stems, and fibers; it also consumes mushrooms and soil [88]. The olive baboon ( Papio anubis ) is usually classified as savanna-dwelling, living in the wide plains of the grasslands, especially those near open woodland, but it also inhabits rainforests and deserts.…”
Section: Methodsmentioning
confidence: 99%
“…Mandrills ( Mandrillus sphinx ) live in tropical rainforests and in gallery forests adjacent to savannas, as well as rocky forests, riparian forests, cultivated areas and flooded forests and streambeds. Forest-dwelling mandrills mostly feed (over 70% year-round) on mechanically protected plant foods such as hard-shell fruits or seeds from the ground [86,87], but will also eat leaves, lianas, bark, stems, and fibers; it also consumes mushrooms and soil [88]. The olive baboon ( Papio anubis ) is usually classified as savanna-dwelling, living in the wide plains of the grasslands, especially those near open woodland, but it also inhabits rainforests and deserts.…”
Section: Methodsmentioning
confidence: 99%
“…We collected GPS points at 30-min intervals, from a position at the spatial center of the group, i.e., at a position where the majority of group members gathered. Data collection in Presbytis potenziani group B and Simias concolor group B was sufficient to use the mimimum convex polygon (MCP) analysis, whereas in all other groups we collected additional data from March to July 2009 to use the fixed kernel contours (FKC) analysis also (Boyle et al 2009;White et al 2010), which provides additional information on the internal size structure of home ranges. This information allows identification of the most intensively used areas within a particular home range.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Small dots (all classes) indicate all individuals that passed through the open area other than the dependent infants, so classes with points located above the line of small dots tended to concentrate in the front of the progression, and classes with points located below the line of small dots tended to be at the rear studies of two Mandrillus species (Hoshino et al 1984;Astaras et al 2008) and Cercocebus mangabeys (Mitani 1989;Range and Fischer 2004). Abernethy et al (2002) also observed short-term subgrouping for at least a few days just after the passage of mandrills through open places, and White et al (2010) observed regular subgrouping of the same horde. We should consider the social organisation and fission-fusion dynamics separately (Aurelli et al 2008;Grueter et al 2012), and account for the possibility that mandrills have more fluid fission-fusion dynamics than typical savannah baboons, as also reported for Guinea baboons (P. papio) (Patzelt et al 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Their large home range (81 km 2 according to the MCP method and based on a six-year study; White et al 2010) and the poor visibility in the dense rainforest make it difficult for field researchers to observe the behaviours of wild Mandrillus populations, meaning that the characteristics of their societies are still unclear. Besides, there are some conflicting arguments about their social systems.…”
Section: Introductionmentioning
confidence: 99%